BEYOND MONITORING : THE IMPACT OF PERFORMANCE MONITORING ON KNOWLEDGE WORKER PRODUCTIVITY - Muneer, Al Dwaikat; Kartinah, Ayupp; Yousef, Ahmad Alolabi (International Association for Quality and Quality of Life Research, 2023)
This study aims to present and test a new conceptual framework to study the significance of employee performance monitoring for knowledge worker productivity in the UAE construction industry. Previous research tends to overlook the mediation effects of stress and knowledge management. In this study, data is collected from 595 executives and non-executives having a minimum of three years of service tenure and a diploma or higher educational qualification from all the seven emirates of the UAE. Because of multivariate analysis, structural equation modelling is employed in the two stages of measurement model accuracy and structural links between research constructs. Research shows that employee performance monitoring directly impacts knowledge worker productivity, as well as the statistically significant impact mediating effect of stress and knowledge management on this relationship. Although stress direct effect on knowledge has a negative beta coefficient, it is still statistically insignificant. Such statistical insignificance reflects that stress does not affect knowledge worker productivity significantly. In this study, the impact of employee performance monitoring on knowledge worker productivity was established. Furthermore, this study found that stress acts as a mediator between employee performance monitoring and knowledge management, and between employee performance monitoring and knowledge worker productivity. Furthermore, this study has other theoretical, empirical, methodological, and practical contributions. This study's results will contribute to policymakers, analysts, and project managers.